Pd-catalyzed benzylic C-H oxidation of cyclotriveratrylene - product diversity - Senthilkumar, B.; Gonnade, Rajesh G.; Ramana, C. V. (Organic & Biomolecular Chemistry, 2015)
The inner-rim functionalization of CTV has been examined by employing Pd-catalyzed benzylic oxidation. The outcome of the oxidation depends upon the solvent and co-oxidants employed. An interesting array of CTV derivatives has been synthesized with a simple change in the conditions.